KETERLAKSANAAN KETERAMPILAN PROSES SAINS DALAM PEMBELAJARAN FISIKA DI SMA NEGERI SE-KOTA PEKANBARU - Meliana Meliana; Yennita Yennita; M. Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : The research aims to obtain information about the process of science skills in learning physics in school year 2013/2014 school classroom eleven senior high school located in the city of Pekanbaru by using the method of survey. The results obtained on the physics teacher as follows: review of preparation of teachers in learning is 72% of teacher overall have done this stage with high category appropriate with the opinion given by head of school. Review of the application of the science process skills by teachers that 72% of teachers overall said had done a science process skills with high category, while the students argued that the teachers applying of science process skills amounted to 62% with enough categories. At this stage of the evaluation obtained that 70% of teachers overall said had done an evaluation which oriented of science process skills with high category, while the students argued that the teachers evaluate 65% with enough categories.Key words : survey, the enforceability of science process skills in the teaching of physics